Factors associated with voice disorders among the elderly: a systematic review - Gois,Amanda Cibelly Brito (2018)
Abstract Introduction During the aging process, natural modifications occur in the larynx and the structures involved in phonation which explain the specific characteristics found in the voices of elderly persons. When, at any moment, a voice fails and there is interference with communication, a voice disorder has occurred. This can generate disadvantages in communicative efficiency and have a negative impact on quality of life, compromising mechanisms of socialization, the maintenance of autonomy, and the sense of well-being. Nevertheless, there appears to be little clarity about which factors are associated with voice disorders in this population, especially from an epidemiological perspective. Objective The present study is a literature review to identify factors associated with voice disorders among the elderly described in population-based studies. Methods A systematic review of electronic databases was carried out. The methodological quality of the studies was analyzed with the Strengthening the Reporting of Observational Studies in Epidemiology guidelines. The research was conducted independently by two researchers. Results Although two articles met the eligibility criteria, none fulfilled all the criteria for the evaluation of methodological quality. According to the two studies selected for this review, factors associated with voice disorders among the elderly included both physical and psychosocial aspects. However, the methodological discrepancies between the studies, particularly in relation to sample selection and the instruments used indicate great variability and compromise the reliability of the results. Conclusion Further prevalence studies and investigations of factors associated with voice disorders in the elderly from an epidemiological perspective, and which involve different cultures, should be carried out.